Regulation of methane production, oxidation, and emission by vascular plants and bryophytes in ponds of the northeast Siberian polygonal tundra. Issue 12 (9th December 2015) - Knoblauch, Christian; Spott, Oliver; Evgrafova, Svetlana; Kutzbach, Lars; Pfeiffer, Eva‐Maria
Abstract: Methane (CH4 ) production, oxidation, and emission were studied in ponds of the permafrost‐affected polygonal tundra in northeast Siberia. Microbial degradation of organic matter in water‐saturated soils is the most important source for the climate‐relevant trace gas CH4 . Although ponds and lakes cover a substantial fraction of the land surface of northern Siberia, data on CH4 fluxes from these water bodies are scarce. Summer CH4 fluxes were measured with closed chambers at the margins of ponds vegetated by vascular plants and in their centers without vascular plants. Furthermore, CH4 and oxygen concentration gradients, stable carbon isotope signatures of dissolved and emitted CH4, and microbial CH4 production and CH4 oxidation were determined. Mean summer fluxes were significantly higher at the margins of the ponds (46.1 ± 15.4 mg CH4  m −2  d −1 ) than at the centers (5.9 ± 8.2 mg CH4  m −2  d −1 ). CH4 transport was dominated by diffusion in most open water sites, but substantial ebullitive fluxes (12.0 ± 8.1 mg CH4  m −2  d −1 ) were detected in one pond. Plant‐mediated transport accounted for 70 to 90% of total CH4 fluxes above emerged vegetation. In the absence of vascular plants, 61 to 99% of the CH4 produced in the anoxic bottom soil was consumed in a layer of the submerged moss Scorpidium scorpioides, which covered the bottoms of the ponds. The fraction of CH4 oxidized was lower at sites with vascular plants since CH4 was predominantly transported through their aerenchyma, thereby bypassing the CH4 oxidation zone in the moss layer. These results emphasize the importance of moss‐associated CH4 oxidation causing low CH4 fluxes from the studied Siberian ponds. Key Points: Methane production, oxidation, and emission were quantified in ponds of the Siberian tundra Methane fluxes above vascular plants are 1 order of magnitude higher than from open water bodies Methane oxidation in submerged moss layers at the pond bottom consumes most of the produced methane